SAT0124 Higher bmi and shorter disease duration are associated with "fibromyalgic" rheumatoid arthritis – evaluation using power doppler ultrasonography. (15th June 2017) - Cheung, P; Lahiri, M
Abstract : Background: Power Doppler ultrasonography (PDUS) can differentiate RA patients who truly have active disease. Patients with persistent joint tenderness may not necessarily have true inflammation; yet composite disease activity indices remain high, leading to treatment escalation. These patients are often referred to having "fibromyalgic RA" where tender joints far exceed that of swollen joints. Objectives: We evaluated the predictors of "fibromyalgic RA (FMRA), " defined as patient-reported tender joint count (TJC) at least 7 greater than PDUS joint count. Methods: Consecutive RA patients were recruited in a tertiary rheumatology centre in Singapore. Patients self-assessed 28 joints for tenderness, followed by blinded PDUS assessment of the corresponding joints. Patients were grouped into either, (i) PDUS joint count > patient-reported TJC, (ii) PDUS joint count = patient-reported TJC (iii) patient-reported TJC > PDUS joint count, (difference <7) (iv) patient-reported TJC > PDUS joint count, (difference ≥7). Group (iv) is defined as FMRA. Predictors of FMRA were evaluated by multinomial logistic regression. Results: Of the 101 patients, 81% were female, 72% Chinese, median age of 53.8 (IQR 48.1;62.4) and disease duration of 6.2 (1.9;8.8) years. Median BMI was 23.6 (20.8;27.0) and DAS28 was 3.2 (2.5;4.2). FMRA patients (15%) had a high median patient-reported TJC of 13 (10;18) but low median PDUS joint count of 1 (0;4). Compared to the other groups, they had higher median DAS28 of 4.6 (3.3;5.2), shorter mean disease duration of 2.3 (0.4;6.8) years, and higher median BMI of 26.9 (23.7;32.2). No differences in mean ESR or proportion of patients with seropositive disease were observed. Using Group (i) as the reference, patients with FMRA were more likely to have a higher BMI (adjusted OR=1.6, 95% CI 1.2; 2.1, p=0.001 for every unit increase) and shorter disease duration (adjusted OR=0.8, 95% CI 0.7;0.98, p=0.03 for every additional year). Age, gender, ethnicity, disease activity (PDUS score) and seropositivity were not significant predictors of FMRA. Conclusions: Higher BMI and shorter disease duration were independent predictors of FMRA. Use of PDUS would be useful in this group, rather than basing treatment decisions on composite disease activity indices alone. Disclosure of Interest: None declared